2019
DOI: 10.1093/rb/rbz005
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mechanical loading facilitated chondrogenic differentiation of rabbit BMSCs in collagen scaffolds

Abstract: Mechanical signals have been played close attention to regulate chondrogenic differentiation of bone marrow mesenchymal stem cells (BMSCs). In this study, dynamic mechanical loading simulation with natural frequencies and intensities were applied to the 3D cultured BMSCs–collagen scaffold constructs. We investigated the effects of dynamic mechanical loading on cell adhesion, uniform distribution, proliferation, secretion of extracellular matrix (ECM) and chondrogenic differentiation of BMSCs–collagen scaffold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 40 publications
(36 reference statements)
1
23
0
Order By: Relevance
“…This study showed that dynamic compression significantly enhanced the synthesis of Col II and aggrecan along with an increase of compressive modulus. Cao et al ( 2019 ) seeded rabbit derived MSCs into collagen scaffolds under 10% compressive sinusoidal strain at 1 Hz frequency, for 2 h/day for 21 days. Starting from the second week of culture, the morphology of MSCs in the dynamic culture group exhibited a rounded chondrocyte-like morphology, whereas cells remained spindle shaped in static culture.…”
Section: Mechanical Cues Affecting Stem Cell Differentiationmentioning
confidence: 99%
“…This study showed that dynamic compression significantly enhanced the synthesis of Col II and aggrecan along with an increase of compressive modulus. Cao et al ( 2019 ) seeded rabbit derived MSCs into collagen scaffolds under 10% compressive sinusoidal strain at 1 Hz frequency, for 2 h/day for 21 days. Starting from the second week of culture, the morphology of MSCs in the dynamic culture group exhibited a rounded chondrocyte-like morphology, whereas cells remained spindle shaped in static culture.…”
Section: Mechanical Cues Affecting Stem Cell Differentiationmentioning
confidence: 99%
“…By altering GelMA concentration, cell proliferation was higher and the gene expression of Col2a1 , Sox9 , and Acan , which were chondrogenic markers, were upregulated with the increase of adhesion ligand density. Similarly, previous research indicated that BMSCs were anchored and required to be attached to the extracellular matrix for survival and proliferation (Cao et al, ). Thus, PEGDA/GelMA hydrogels with more adhesion ligands may provide a more native surface for cellular attachment.…”
Section: Discussionmentioning
confidence: 74%
“…In our study, the 3D scaffold of adhesion ligand density was changed by using different ratios of GelMA in the PEGDA/GelMA hydrogels. Similarly, previous research indicated that BMSCs were anchored and required to be attached to the extracellular matrix for survival and proliferation (Cao et al, 2019). As BMSCs were anchorage dependent, they might primarily be affected by ECM adhesion ligands (Chen, Reuveny, & Oh, 2013;Lu, Lee, Lam, Tabata, & Mikos, 2016).…”
Section: Discussionmentioning
confidence: 84%
“…The pH of the collagen solution (2 wt%) was adjusted to about 7 with 1 M NaOH solution. The prepared neutral collagen gel was added with rBMSCs cell suspension and different concentrations of PRP and LyPRP solution to make the final cell concentration reach to 3 × 10 6 cells/ml [ 21 ]. The composite hydrogels blended with rBMSCs were injected into the above-mentioned self-made silicone molds and incubated at 37°C until the gels formed.…”
Section: Methodsmentioning
confidence: 99%